Sedation - analgesia - muscle relaxant - withdrawal and delirium practices in pediatric intensive care units in Türkiye - Esra Koçkuzu; Ali Korulmaz; Ümit Altuğ; Gürkan Bozan; Dinçer Yıldızdaş (The Turkish Journal of Pediatrics, 2024)
Background. Pain and sedation management is an integral part of pediatric intensive care practice. Sedoanalgesia management must be balanced in order to optimize comfort and avoid complications. In order to achieve this balance, sedoanalgesia management needs to be clarified in pediatric intensive care units (PICU). With this study, we aimed to investigate sedation, analgesia, withdrawal and delirium practices, pharmacologic agent preferences, and current experiences and practices in scoring systems in PICUs in Türkiye.